Social behavior of scouting groups in vocational schools in Babylon Governorate center - Samer Ayed Kadhim (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Importance of this study stems from its focus on advanced scouts and advanced guides in vocational schools. It aims to understand their social behavior and assess their potential for improvement. Given importance of scouting in vocational schools, the research problem lies in the variation in social behavior levels among advanced scout and advanced guide groups within these schools, and to identify the reasons for this variation. Study also aims to develop a social behavior scale for scouting groups, identify the level of social behavior within these groups in vocational schools, and understand the behavior of vocational students participating in scouting groups according to gender. The researcher employed a descriptive methodology, utilizing survey techniques, case studies, and comparative studies. Study sample consisted of scout troops from vocational schools in Babylon Governorate center advanced scouts and advanced guides. The study concluded that the scout troops both scouts and guides exhibited high levels of social behavior. The guide troops demonstrated even higher levels of social behavior than the scout troops . The recommendations include holding a successful scout day each month to practice various scouting activities and creating educational opportunities to instill social and educational values and train positive behavior.